2014
DOI: 10.1007/s10120-014-0453-0
|View full text |Cite
|
Sign up to set email alerts
|

HER2 testing in paired biopsy and excision specimens of gastric cancer: the reliability of the scoring system and the clinicopathological factors relevant to discordance

Abstract: Background Inclusion of trastuzumab in chemotherapy regimens is advantageous for patients with advanced or metastatic gastric cancer who overexpress HER2. Therefore, accurate assessment of HER2 status in tumor tissue is critical when weighing treatment options. Methods We examined HER2 expression in 180 paired endoscopic biopsy and surgical excision specimens of gastric cancers via immunohistochemistry (IHC). Equivocal IHC results (IHC 2?) were resolved by HER2 fluorescence in situ hybridization (FISH). The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
0
21
0
1
Order By: Relevance
“…But Saito et al [10], in a series of 224 patients, they found 21% of tissues were HER2-positive. Furthermore, Huang et al determined only a proportion of 7.8% of HER2-positive in fourteen biopsy and surgical specimens [8]. However, in the study of Rajagopal et al, in 60 cases, positive HER2 expression was observed only in In their study, they demonstrated a significant difference in the overexpression of HER2/neu in gastric tumors.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…But Saito et al [10], in a series of 224 patients, they found 21% of tissues were HER2-positive. Furthermore, Huang et al determined only a proportion of 7.8% of HER2-positive in fourteen biopsy and surgical specimens [8]. However, in the study of Rajagopal et al, in 60 cases, positive HER2 expression was observed only in In their study, they demonstrated a significant difference in the overexpression of HER2/neu in gastric tumors.…”
Section: Discussionmentioning
confidence: 46%
“…The HER2 protein is a member of the epidermal growth factor receptor family and is coded by HER2/neu gene located on the long arm of chromosome 17 [8]. The product is a 185 kD transmembrane glycoprotein [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, HER2 status of 36 patients was evaluated in biopsy specimens which have been shown to be highly consistent with surgical specimens [3234]. To predict HER2 precisely, 4 tumor-containing fragments were recommended [35].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of HER2 status in GC is challenging because of the protein’s affinity for being heterogeneously expressed [46]. For endoscopic biopsy specimens, it is a far more serious issue in that biopsy specimens are less manageable than resected specimens in HER2 assessment due to unpredictable tumor tissue amount.…”
Section: Introductionmentioning
confidence: 99%